Analysis of Waste Management on Community Economic Empowerment in the Waste Bank Program of Medan Belawan District - Ade Linia Br Bangun; Alpindo Febrian; Alfiqri Bukhori; Ahmad Fadlan (International Journal of Management, Economic and Accounting, 2025)
Waste is one of the environmental problems that continues to grow along with the increase in community activities, especially in coastal areas such as Medan Belawan District. This study aims to analyze waste management in relation to community economic empowerment through the Berkah Waste Bank Program. The approach used is a descriptive quantitative approach with data collection techniques through field observations, questionnaire distribution, and questionnaires to the communities involved in the program. The results of the study show that waste management through the waste bank program has a positive impact on the citizens' economy, such as increasing income, increasing awareness of the importance of a clean environment, and opening up recycling-based business opportunities. The active participation of the community is a major factor in the success of this program. These findings show that proper waste management can be an instrument for sustainable economic empowerment at the local level.